A Needs-Based Analysis and Development of an English Language Skills Module for Front Office Employees at a Local Hotel in Batam - Zaki, Leil Badrah; Purba, Angelina Trisnauly; Nugraha, Hendra; Febria, Desty (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study presents a needs-based analysis and the development of an English language skills module specifically designed for front office employees at a local hotel in Batam, Indonesia. Using a Research and Development (R&D) approach and the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the module was developed based on Hutchinson & Waters' needs analysis framework. Data were collected through interviews with four front office employees, while two experts—a hotel manager and an ESP lecturer—validated the module. The analysis revealed that employees primarily struggled with listening comprehension, speaking fluency, and confidence when interacting with international guests. The findings imply that conducting a thorough needs analysis is crucial for developing effective English training materials in the hospitality industry. Without understanding the specific language challenges faced by front office employees, training programs risk being irrelevant or ineffective. This study highlights that a conducted needs analysis leads to more targeted, practical modules that directly address real workplace communication problems. It also underscores the importance of aligning training content with employee needs to improve service quality, enhance guest satisfaction, and strengthen the hotel’s role in supporting regional tourism growth.